2017
DOI: 10.1093/reseval/rvw025
|View full text |Cite
|
Sign up to set email alerts
|

‘Your comments are meaner than your score’: score calibration talk influences intra- and inter-panel variability during scientific grant peer review

Abstract: In scientific grant peer review, groups of expert scientists meet to engage in the collaborative decision-making task of evaluating and scoring grant applications. Prior research on grant peer review has established that inter-reviewer reliability is typically poor. In the current study, experienced reviewers for the National Institutes of Health (NIH) were recruited to participate in one of four constructed peer review panel meetings. Each panel discussed and scored the same pool of recently reviewed NIH gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 51 publications
(70 reference statements)
3
41
0
Order By: Relevance
“…Indeed we find that monitoring of the scoring patterns can motivate explicit “policing,” whereby individual meeting members call into question the legitimacy of a score, and by extension, the legitimacy of an assigned reviewer’s own expertise (Pier et al, 2017). The scoring process is thus of immediate consequence to the social and professional standings of the meeting participants as they construct their professional expertise in situ during the meeting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed we find that monitoring of the scoring patterns can motivate explicit “policing,” whereby individual meeting members call into question the legitimacy of a score, and by extension, the legitimacy of an assigned reviewer’s own expertise (Pier et al, 2017). The scoring process is thus of immediate consequence to the social and professional standings of the meeting participants as they construct their professional expertise in situ during the meeting.…”
Section: Discussionmentioning
confidence: 99%
“…Research on grant peer review panel interactions has almost exclusively relied on ethnographic interviews and participant observation (Ahlqvist et al, 2013; Lamont, 2009) rather than close analysis of unfolding interaction. Indeed, research directly examining discourse and interaction in review panel meetings has only recently emerged (Gallo, Carpenter, & Glisson, 2013; Pier, Raclaw, Kaatz, Carnes, Nathan, & Ford, 2017; Authors, 2015). As part of a larger project aimed at documenting interactional practices inside the “black box” of peer review meetings, 1 in this paper we focus on how participants in these settings use laughter as a resource to manage the divergence of evaluative positions that characterizes the give and take of joint grant evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pier et al provides a full description of our methodology. 1 Participant-reviewers evaluated R01 applications previously reviewed by study sections within NIH's National Cancer Institute. Applications were donated by Principal Investigators identified using NIH's public access database, then de-identified and re-identified by the research team.…”
mentioning
confidence: 99%